Strategi Pemberdayaan Pemuda Melalui Pelatihan Keorganisasian: Studi Kasus pada Karang Taruna Desa Sukarame Kecamatan Pacet, Kabupaten Bandung, Jawa Barat 40385: Pengabdian - Wanda Sofianti; Husni Munawar; Annisa Zahra Rahmayati; Silvia Nurfadilah; Siti Nur Jamilah; Syahla Nur Fikriyyah; Anjani; Raisa Ratna Khodijah; Jaomal Komara; Djufran D Hi Kasim; Vera Martikasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study comprehensively analyzes strategies for empowering youth through organizational training, using a case study of Karang Taruna in Sukarame Village, Pacet District, Bandung Regency, West Java. Youth empowerment is a critical lever for sustainable community development; however, rural youth often face constraints in managerial capability, leadership experience, and program execution. The research adopts a qualitative single-case design combining in-depth interviews (youth leaders, members, village officials), focus group discussions, participant observation during training sessions, and document analysis (training modules, minutes, budgets, program reports). Findings show that a training design grounded in participatory learning, mentoring, and project-based application—supported by digital tools—improves leadership, public speaking, teamwork, basic project management, and civic engagement. Using a logic-model lens (input–process–output–outcome–impact) and Kirkpatrick’s evaluation framework, the study evidences gains in attendance, skill demonstration, program execution rates, and stakeholder collaboration. Enablers include strong social capital, village government support, and peer mentors; barriers include funding limitations, scheduling conflicts with school/work, facilitator turnover, and uneven digital access. The paper proposes a six-pillar strategy (participation, mentoring, collaboration, micro-grants, digitization, M&E) and a scalable implementation roadmap for rural youth organizations.